Evaluation of the efficacy and safety of text messages targeting adherence to cardiovascular medications in secondary prevention: The txt2heart Colombia randomised controlled trial protocol (2023)
Introduction Anti-platelet therapy, angiotensin-converting enzyme inhibitors/angiotensin II receptor blockers, beta-blockers and statins are cost-effective in patients with atherosclerotic cardiovascular diseases (ASCVD) for reducing the risk of ASCVD events. Unfortunately, there is abundant evidence that adherence to these cardiovascular medications is far from ideal. A recent Cochrane review showed a potential beneficial effect of Short Message Service (SMS) interventions on adherence to medication in ASCVD patients. Methods and analysis The txt2heart study is a pragmatic randomised single-blind controlled trial. The objective is to evaluate the efficacy and safety of an intervention with SMS messages delivered by mobile phones to improve adherence to cardiovascular medications in patients with ASCVD. The intervention consists of behavioural techniques delivered via SMS. The primary outcome is change in blood serum low-density lipoprotein cholesterol levels as an indicator of adherence to statins. Secondary outcomes will include systolic blood pressure as an indicator of adherence to blood-lowering therapies and heart rate as an indicator of adherence to beta-blockers, urine levels of 11-dehydrothromboxane B2, self-reported adherence to cardiovascular medications and rates of cardiovascular death or hospitalisation due to cardiovascular disease. Ethics and dissemination The study will be performed in compliance with the protocol, regulatory requirements, Good Clinical Practice and ethical principles of the Declaration of Helsinki. The Ethics Committee of Fundación Cardiovascular de Colombia evaluated and approved the trial. The txt2heart Colombia trial aims to provide robust evidence to evaluate whether SMS messages delivered through mobile telephones change the behaviour of Colombian patients who have suffered a cardiovascular event. Trial results will be presented to the local health authorities, and if the intervention is effective and safe, we hope this strategy will be implemented quickly because of its low cost and wide-reaching impact on the population. Trial registration number NCT03098186. © Author(s) (or their employer(s)) 2019.